Interior design's social compact: Key to the quest for professional status - Anderson, Barbara G.; Honey, Peggy L.; Dudek, Michael T. (My University, 2009)
The expectation that all interior design professionals will embrace and embody this social compact in the near future is idealistic but not unrealistic. There are many interior designers and interior design educators for whom this proposed social compact will be reaffirming because they already embody this ethic in their work. We believe the transformation of the profession will happen both within the academy and within the profession itself. Interior design educators will play a significant role in causing the necessary shift away from arguing professional expertise toward embracing the social importance and value of our work. When all interior designers value and act with good faith to enhance the quality of life through their work, society will bestow professional status on interior designers because they will deserve it. Interior design educators must redefine the profession's role in society by educating new interior designers to understand and value the profession's obligation to providing a unique and meaningful service to society, one that contributes to interdependence and thus has value beyond the economic welfare of the practitioner and client. Interior designers can be full participants in the efforts to advance humanity toward maturity (Elgin 2001); in what Edwards (2005) calls the "sustainability revolution"; and in what Berry (1999) calls "the great work." Interior designers are poised to take full advantage of the opportunities presented by the "conceptual age" that Daniel Pink (2005) says will reward those who focus "on meeting the aesthetic, emotional, and spiritual demands of a prosperous time" (246). Soon after interior design accepts its social compact as the guiding force for all that it does, we believe the interior design profession's self-image—and eventually its public image—will be transformed. Educators must take the lead in communicating the profession's potential to support the common good. When practitioners and educators come together to embrace and embody the profession's social compact we will begin to understand the whole range of work that now falls under the umbrella of interior design in a new and inclusive way. When the interior design profession as a whole finds significance and meaning in its work and is committed to fulfilling a unique and valuable role in society, then our common commitment to a significant purpose will bind us together into a confident, recognized, and valued profession.
Keywords: Interior design; Social responsibility; Social compact; Profession; Interiors; Sustainability